Popular culture, contemporary trends and social identities in Kenyan youth fiction - Oduor, Vincent Odhiambo; Omuteche, Jairus; Yenjela, David W. (Nairobi Journal of Humanities and Social Sciences, 2022)
This article examines the extent to which contemporary popular cultural trends influence the formation of social identities among the youth. In light of this, the study addresses the question of intergenerational sexual relationship, the psycho-social impact of technoculture on youth identity formation and how HIV/AIDS discourse is used to (re)construct sexual behaviour. The study is informed by the idea that youths are always among the first to experience, first-hand, the problems and possibilities of the successive waves of technical and economic modernization sweeping through capitalist societies (Willis, 2003). At the same time, youths are seen as a part of society that is most likely to engage in the process of cultural borrowing which is disruptive of the reproduction of traditional cultural practices, from modes of dress to language, aesthetics and ideologies (Heaven & Tubridy, 2002). This is bound to affect their identity formation. The study is qualitative, involving close reading of Elizabeth Kabui’s Was Nyakeeru my Father (2014), Florence Mbaya’s Sunrise at Midnight (2014), Bill Ruto’s Death Trap (2005), Carolyne Adalla’s Confessions of an Aids Victims (1993), Moraa Gitaa’s The Shark Attack (2014) and Kingwa Kamencu’s To Grasp at a Star (2005). The analysis is guided by postmodern literary theory in the process of its enquiry.